2009
DOI: 10.2337/db08-0877
|View full text |Cite
|
Sign up to set email alerts
|

Association Analysis of Variation in/NearFTO,CDKAL1,SLC30A8,HHEX,EXT2,IGF2BP2,LOC387761, andCDKN2BWith Type 2 Diabetes and Related Quantitative Traits in Pima Indians

Abstract: OBJECTIVE-In recent genome-wide association studies, variants in CDKAL1, SLC30A8, HHEX, EXT2, IGF2BP2, CDKN2B, LOC387761, and FTO were associated with risk for type 2 diabetes in Caucasians. We investigated the association of these single nucleotide polymorphisms (SNPs) and some additional tag SNPs with type 2 diabetes and related quantitative traits in Pima Indians. RESEARCH DESIGN AND METHODS-Forty-sevenSNPs were genotyped in 3,501 Pima Indians informative for type 2 diabetes and BMI, among whom 370 had mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
95
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(110 citation statements)
references
References 39 publications
11
95
4
Order By: Relevance
“…The SNPs rs7754840 was only 216-bp downstream from rs10946398. Although rs7754840 and rs10946398 are in complete linkage disequilibrium in the Hispanic American population (r 2 = 1.0) , Japanese population (Horikoshi et al, 2007), Korean population (D' = 1, r 2 = 1) (Lee et al, 2008), and Pima Indian population (Rong et al, 2009), the rs7754840 variant was found in a region with extensive linkage disequilibrium differences between multiple groups from South-East Asia (Chinese, Malay and Indian) recruited for the Singapore Genome Variation Project (Teo et al, 2009).…”
Section: A B C Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SNPs rs7754840 was only 216-bp downstream from rs10946398. Although rs7754840 and rs10946398 are in complete linkage disequilibrium in the Hispanic American population (r 2 = 1.0) , Japanese population (Horikoshi et al, 2007), Korean population (D' = 1, r 2 = 1) (Lee et al, 2008), and Pima Indian population (Rong et al, 2009), the rs7754840 variant was found in a region with extensive linkage disequilibrium differences between multiple groups from South-East Asia (Chinese, Malay and Indian) recruited for the Singapore Genome Variation Project (Teo et al, 2009).…”
Section: A B C Discussionmentioning
confidence: 99%
“…CDKAL1 rs7754840 was significantly associated with type 2 diabetes in the Korean population (Lee et al, 2008), Finnish men (Stancáková et al, 2008), but not in Asian Indian Sikhs (Sanghera et al, 2008). No association was found between CDKAL1 variants and type 2 diabetes in the Austrian population (Cauchi et al, 2008a), Norwegian population-based sample (Hertel et al, 2008) or Pima Indians (Rong et al, 2009). …”
Section: Introductionmentioning
confidence: 98%
“…The association of FTO variant with T2DM has been reported in several studies. 1,33 Furthermore, a meta-analysis of seven association studies in Caucasians reported positive correlations with metabolic traits, including plasma insulin and glucose levels. 34 However, these associations disappeared on adjustment for BMI, suggesting that the genetic susceptibility for T2DM and metabolic traits was largely due to the effect on BMI.…”
Section: à2mentioning
confidence: 99%
“…2) the data from the genetic studies examining type 2 diabetes Those showing significant (black circles) and non-significant (white circles) association with BMI in Japanese are depicted. SNP rs numbers of individual loci are as follows: rs2815752 for NEGR1, rs10913469 for SEC16B, rs4854344 for TMEM18, rs7647305 for ETV5, rs10938397 for GNPDA2, rs2844479 for NCR3, rs6265 for BDNF, rs10838738 for MTCH2, rs7138803 for BCDIN3D, rs4788102 for SH2B1, rs6499640 for FTO(1), rs9939609 for FTO(2), rs12970134 for MC4R and rs29941 for KCTD15 association at the FTO locus [3,11,24,[32][33][34][35][36][37][38][39][40][41][42], our aim being to evaluate the relationship between BMI in the control group (or derived population) and the OR for type 2 diabetes. We detected no apparent relationship between the tested variables (p=0.15 for East Asians and p=0.41 for Europeans; Fig.…”
Section: Association Of Obesity Susceptibility Snps With Type 2 Diabetesmentioning
confidence: 99%